2017
DOI: 10.1002/2327-6924.12452
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy in the urgent care setting

Abstract: Background An increasing number of Americans are using urgent care (UC) clinics due to: improved health insurance coverage, the need to decrease cost, primary care offices with limited appointment availability, and a desire for convenient care. Patients are treated by providers they may not know for episodic illness or injuries while in pain or not feeling well. Treatment instructions and follow‐up directions are provided quickly. Purpose To examine health literacy in the adult UC population and identify patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…The elderly population usually had less opportunities and approaches to access to health education. Overall, the Chinese elderly population had limited access to education during their youth, which coincided with the findings of some previous studies [2, 11, 12, 21]. Few studies have highlighted a relationship between BMI and HL.…”
Section: Discussionsupporting
confidence: 85%
“…The elderly population usually had less opportunities and approaches to access to health education. Overall, the Chinese elderly population had limited access to education during their youth, which coincided with the findings of some previous studies [2, 11, 12, 21]. Few studies have highlighted a relationship between BMI and HL.…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, studies have shown that limited health literacy is linked to poor health outcomes (Baskaradoss, 2016;Cheng, Bauer, Downs, & Sanders, 2016;Fonseca, Silva, & Canavarro, 2017;McNaughton et al, 2014;Wu et al, 2017). This is especially concerning for vulnerable populations such as that of our sample since limited health literacy has been associated with low income and socioeconomic status, lower levels of education, racial/ethnic minorities, older age, Spanish speakers, immigrants, and cognitively impaired individuals (Alberti & Morris, 2017;Baker, Wolf, Feinglass, & Thompson, 2008;Cajita, Cajita, & Hae-Ra, 2016;Fonseca et al, 2017;Hahn et al, 2015;McNaughton et al, 2014;Walker, Pepa, & Gerard, 2010). By assessing health literacy at the needs assessment phase, students will be able to consider community members' level of health literacy in the cultural tailoring process, in addition to considering social, cultural, and developmental needs.…”
Section: Discussionmentioning
confidence: 81%
“…In general, older age has consistently been associated with low health literacy, and some studies describe those 65 years and older as being particularly affected. 4 , 5 , 21 26 Regarding race/ethnicity, multiple US studies have demonstrated a consistent pattern of low health literacy among racial/ethnic minorities including Hispanic and African American groups. 5 , 7 , 20 , 21 , 23 , 27 , 28 In contrast, Whites and Asian/Pacific Islanders were found to have higher rates of adequate health literacy.…”
Section: Patient-level Factors Associated With Health Literacymentioning
confidence: 99%